Surgical Management of Large Mediastinal Masses–12 Years’ Experience in Apollo Hospitals Dhaka - Zahangir, NM; Hasan, MK; Basak, RK; Meher, T; Alam, NS; Hossain, MN; Khan, A; Ahmed, N; Ahmed, S; Haider, MZ (Pulse, 2018)
Objective: The aim of this study was to evaluate the role of surgical treatment for large mediastinal tumors. A retrospective study was done from 6.8.2005 to 11.5.2017. Total 39 patients were included in this study. Age range was from 7 months to 70 years. Male was 24 and female was 15. Background: Most of the tumours were thymoma (12 cases). Others were thymoma with myasthenia gravis in 3 cases, Thymic carcinoma 2 cases, Nodular sclerosing Hodgkin’s lymphoma in 1 case, Schwannoma in 3 cases, Cystic mass in 5 cases, Schwannoma with cystic degeneration in 1 case, Fibromyxoma in 1 case, Dermoid in 4 cases, Teratoma in 3 cases, Fibrosing mediastinitis in thymic mass in 1 case, Lymphoid hyperplasia in 1 case, Malignant Mesenchymal tumour in 1 case, Myxoid Liposarcoma in 1 case. Method: Surgical exposure varies from sternotomy in 22 cases, to clamshell incision in 1 case, posterolateral thoracotomy in 14 cases and anterolateral thoracotomy in 2 cases. Superior Venacava was injured in 1 case, repaired successfully by 6/0 prolene controlled by partial clamp. Some of the mediastinal mass needed careful dissection from lung, pleura, encircling distal aortic arch and proximal part of left subclavian artery, encircling left brachiocephalic vein. 1 case needed reconstruction of sternum with prolene mesh, marsupialization was done in 2 cases, adjacent pleura, fatty tissue, part of pericardium was removed in 5 cases. Lobectomy was needed in 1 case. In 1 case, recurrence of fibrosing mediastinitis needed steroid therapy. Extensive growth of the tumour which involved surrounding vital structures was decided not to proceed for excision in 2 cases. Results: Overall five-years survival rate was 94.87% .2 patients of the series died due to disease process as they were cases of advanced malignant mediastinal mass. Conclusion: Surgical treatment for mediastinal mass specially involving surrounding structures though challenging, gives good outcome. Pulse Vol.10 January-December 2017 p.12-17